Mode of delivery, mutans streptococci colonization, and early childhood caries in three- to five-year-old Thai children - Pattanaporn K. (2014)
Objective To investigate whether mode of delivery is associated with mutans streptococci (MS) colonization and early childhood caries (ECC) in preschool Thai children. Methods Three hundred and fifty mothers and their 3- to 5-year-old children (184 born vaginally and 166 born by Caesarean section) participated in the study. Data included a dental examination, MS colonization assessed by the Dentocult® SM Strip Mutans method, and a questionnaire survey of family socio-demographic information, as well as children's birth history, dietary habits, and oral health practices. Results Overall, ECC prevalence was 56% in 3-year-old and 78% in 5-year-old Thai children. Compared to children delivered by C-section, vaginally born children experienced increased ECC prevalence (73.8% versus 59.6%; P = 0.009) and were more likely to have higher MS scores (OR = 1.8, 95% CI = 1.1-2.9), adjusting for mother's gestational age, MS score, feeding practice habits; child's age and tooth brushing habits. Children's MS scores were highly correlated with their mothers' MS scores (P < 0.001). Additionally, children's age, MS colonization, and mothers' prechewing feeding habits were the most significant risk indicators for ECC in Thai children. Conclusion Our findings suggest that mode of delivery is significantly correlated with MS colonization and caries outcomes in young Thai children. Future studies are needed to further understand the possible biological mechanisms linking mode of child delivery to the colonization of cariogenic microbiota and development of ECC. © 2012 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.